2006
DOI: 10.1530/rep.1.01074
|View full text |Cite
|
Sign up to set email alerts
|

TGF-β superfamily members and ovarian follicle development

Abstract: In recent years, exciting progress has been made towards unravelling the complex intraovarian control mechanisms that, in concert with systemic signals, coordinate the recruitment, selection and growth of follicles from the primordial stage through to ovulation and corpus luteum formation. A plethora of growth factors, many belonging to the transforming growth factor-b (TGF-b) superfamily, are expressed by ovarian somatic cells and oocytes in a developmental, stage-related manner and function as intraovarian r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

19
807
0
32

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 1,061 publications
(858 citation statements)
references
References 142 publications
19
807
0
32
Order By: Relevance
“…Coexpressed with its receptor, AMH appears to be an autocrine factor in regulating primate ovarian follicular development. This stage-dependent expression of a ligand and its receptor has been noted for other TGFβ superfamily members in human follicles [37]. Studies are ongoing to further unravel the molecular mechanisms of AMH signaling in the primate follicle by gene silencing.…”
Section: Discussionmentioning
confidence: 65%
“…Coexpressed with its receptor, AMH appears to be an autocrine factor in regulating primate ovarian follicular development. This stage-dependent expression of a ligand and its receptor has been noted for other TGFβ superfamily members in human follicles [37]. Studies are ongoing to further unravel the molecular mechanisms of AMH signaling in the primate follicle by gene silencing.…”
Section: Discussionmentioning
confidence: 65%
“…53,54 Members of this family have important roles in proliferation, differentiation, adhesion, motility and apoptosis. Many are involved in embryonic development as well as in adult tissue homeostasis.…”
Section: Discussionmentioning
confidence: 99%
“…In the current study, we observed an increase in less acidic FSH isoforms during the final stages of follicle development in cows with an ovulatory follicle, associated with significantly greater circulating inhibin A and estradiol concentrations. Increased output of inhibin by the selected dominant follicle may upregulate LH-induced androgen secretion that is required to sustain a high level of 210 estradiol secretion from the preovulatory follicle (30).…”
Section: A Concentrations 195mentioning
confidence: 99%
“…A prompt resumption of ovulatory activity following parturition is desirable; cows that have an early commencement of luteal activity have an improved likelihood of conception after breeding (4). 30 Timing of the first postpartum ovulation is correlated with timing of the onset of recovery from the negative energy balance (NEB) nadir (5,6). Infusion of exogenous pulses of LH during the first postpartum follicle wave in dairy (7) and beef (8) cows increased the likelihood of ovulation.…”
Section: Introduction 20mentioning
confidence: 99%